Genetically supported causality between gut microbiota, immune cells, and ischemic stroke: a two-sample Mendelian randomization study - Shuai, Han; Wang, Zi; Xiao, Yinggang; Ge, Yali; Mao, Hua; Gao, Ju (Frontiers in Microbiology, 2024)
Background: Previous studies have highlighted a robust correlation between gut microbiota/immune cells and ischemic stroke (IS). However, the precise nature of their causal relationship remains uncertain. To address this gap, our study aims to meticulously investigate the causal association between gut microbiota/immune cells and the likelihood of developing IS, employing a two-sample Mendelian randomization (MR) analysis. Methods: Our comprehensive analysis utilized summary statistics from genome-wide association studies (GWAS) on gut microbiota, immune cells, and IS. The primary MR method employed was the inverse variance-weighted (IVW) approach. To address potential pleiotropy and identify outlier genetic variants, we incorporated the Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) technique, along with MR-Egger regression. Heterogeneity was assessed using Cochran's Q-test. Additionally, leave-one-out analysis was conducted to pinpoint any individual genetic variant influencing the observed causal associations. Finally, a reverse MR analysis was performed to explore the potential of reverse causation.Results: Our investigation revealed four gut microbial taxa and 16 immune cells with a significant causal relationship with IS (p < 0.05). Notably, two bacterial features and five immunophenotypes were strongly associated with a lower IS risk: